(untitled) (The Journal of Medicine, Humanity and Media, 2023)
The third session of the 6th International Conference on Medicine, Humanities and Media (MHM 2023): Behavioral Research under the Influence of Digital Health Information convened at the School of Journalism and Communication, Peking University on November 4, 2023. The proceedings were presided over by Tang Jiamei(Professor of the School of Journalism and Communication, Guangdong University of Foreign Studies). Jiang Li (Associate Professor of the Department of Media and Communication, City University of Hong Kong), and Jiang Shaohai (Assistant Professor of the Department of Communication and New Media, National University of Singapore), were the keynote speakers. A total of seven panelists presented insightful and innovative papers demonstrating the relationship between digital health information and behavior change across diverse social issues.